Pelatihan Pemanfaatan Shortcut Microsoft Excel untuk Meningkatkan Efisiensi Pengolahan Data bagi Siswa SMK - Fakhriani Ekawati; Yusup Indra Wijaya; Hoiriyah Hoiriyah (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The development of information technology requires vocational high school students to possess digital skills that align with industry needs. One of the essential competencies is the ability to use Microsoft Excel effectively and efficiently. However, many students still rely heavily on mouse-based operations, resulting in less efficient data processing. This community service program aimed to improve students’ understanding and skills in utilizing Microsoft Excel keyboard shortcuts to enhance data processing efficiency. The activity was conducted at SMK Negeri 1 Banjarmasin and involved 15 participants. The implementation methods included lectures, demonstrations, hands-on practice, case studies, and evaluations using Likert-scale pre-tests and post-tests. The results indicated that the average participant score increased from 69.13 in the pre-test to 77.20 in the post-test, representing an improvement of 11.67%. These findings demonstrate that the training effectively enhanced students’ ability to utilize Microsoft Excel shortcuts and improved their readiness to meet technology-driven workplace demands.